Neutralizing antibodies for orthobunyaviruses in Pantanal, Brazil. - Alex Pauvolid-Corrêa; Zilca Campos; Raquel Soares; Rita Maria Ribeiro Nogueira; Nicholas Komar (Public Library of Science (PLoS), 2017)
The Pantanal is a hotspot for arbovirus studies in South America. Various medically important flaviviruses and alphaviruses have been reported in domestic and wild animals in the region. To expand the knowledge of local arbovirus circulation, a serosurvey for 14 Brazilian orthobunyaviruses was conducted with equines, sheep and free-ranging caimans. Sera were tested for specific viral antibodies using plaque-reduction neutralization test (PRNT). Monotypic reactions were detected for Maguari, Xingu, Apeu, Guaroa, Murutucu, Oriboca, Oropouche and Nepuyo viruses. Despite the low titers for most of the orthobunyaviruses tested, the detection of monotypic reactions for eight orthobunyaviruses suggests the Pantanal as a region of great orthobunyavirus diversity. The present data, in conjunction with previous studies that detected a high diversity of other arboviruses, ratify the Pantanal as an important natural reservoir for sylvatic and medically important arboviruses in Brazil.